Incidence of Green-gram Diseases and Alternaria Leaf Blight of Albizia procera in Agroforestry Systems - Kumar, Anil; Chaturvedi, O.P.; Singh, R. (Indian Journal of Agroforestry, 2020)
A study on effect of a babul (Acacia nilotica) windbreak on green-gram diseases and of intercropping on alternaria leaf blight of safed siris (Albizia procera) was conducted. Severity of cercospora leaf spot of green-gram increased and symptoms of yellow mosaic were masked in shade of the wind-break. Severity of alternaria leaf blight of safed siris increased by inter-cropping with wheat and mustard. Sharing of diseases among component crops of the systems was absent, except alternaria infection was noticed on component crops of siris based agroforestry system.